P82 Lung clearance index (LCI) and genotype-phenotype correlations in Primary Ciliary Dyskinesia (PCD). (12th November 2015) - Irving, S; Dixon, M; Ollosson, S; Hogg, C; Shoemark, A; Bush, A
Abstract : Introduction and objectives: Mutation type may affect clinical phenotype in PCD, as shown by differences in forced expiratory volume in 1 s (FEV1 ) (AJRCCM 2015;191:316–324). LCI, measured using multi-breath washout (MBW) is raised in PCD (AJRCCM 2013;188:545–549) but the relative sensitivities of the two physiological measurements is disputed (Thorax 2015;70:339–345, and 305–306). We hypothesised that LCI would be more sensitive to genotype-phenotype differences in PCD. Methods: MBW (using sulphur hexafluoride MBW with a photoacoustic gas analyser) and spirometry were performed in 77 PCD patients (mean age 16.4 years (range 4–62.2), 33 males, mean FEV1 z score -2.09 (range - 5.33–1.59)). 44 had outer dynein arms (ODA) defects, or both inner (IDA) and ODA, 18 had microtubular defects (either transposition or microtubule disorganisation with absent IDA), 15 had normal ultrastructure (diagnosis made on either genetics (n = 10), low nasal NO, clinical phenotype and consistent dyskinesia on light microscopy (n = 1), or low nasal NO, clinical phenotype and an affected sibling (n = 3)). There was no significant difference in age or gender composition between the 3 groups. Results: Patients with normal ultrastructure had significantly higher FEV1 and lower LCI, indicating milder disease. Those with ODA +/- IDA had a more normal LCI than those with microtubular defects (Figure 1 ), but similar FEV1 . Conclusions: PCD patients with normal ultrastructure have the milder disease, and those with microtubular defects more severe. Differences were more apparent on LCI than FEV1, suggesting LCI may be more sensitive to worse distal small airway disease in PCD.